Factors influence women's participation in entrepreneurship / Nur Sufiakhofi Zekaria and Radiana Rajali - Zekaria, Nur Sufiakhofi; Rajali, Radiana (2019)
In this chapter we will discuss briefly about the study based on the topic chosen which is the Factors influencing Women Participation in entrepreneurship. Moreover, in this chapter will also include the background of the study that explains precisely what the study is about followed by problem statement. Then, this chapter as well talks about the research objectives, research question, research objectives, research hypotheses, the scope of study, significance of study and definition of term and lastly chapter summary. Women entrepreneurship is the process in which women initiate a business, gather all resources, under takes risks, face challenges provide employment to others and manages the business independently (Bbmatra, 2018). With that said, it is to create an environment where women can influence innovative ideas into businesses. Furthermore, also, it is said that women have filled over half the population of the world that is why they are regarded as the better half of the society (Francis, 2018). Although, women in the olden days of society were only restrained between the four walls of a house and is subjected to preform household duties. However nowadays, women are much more than that many have indulged themselves in participating various activities in terms of academic, political, administration, social work and others related.